Epithelial cell lysates induce ExoS expression and secretion by Pseudomonas aeruginosa. Issue 8 (6th March 2018) - Hritonenko, Victoria; Metruccio, Matteo; Evans, David; Fleiszig, Suzanne
Abstract: The type three secretion system (T3SS) is important for the intracellular survival of Pseudomonas aeruginosa . Known T3SS inducers include low Ca 2+, serum or host cell contact. Here, we used corneal epithelial cell lysates to test if host cytosolic factors could also induce the T3SS. Invasive P. aeruginosa strain PAO1 was exposed to cell lysates for 16 h, and expression of T3SS effectors determined by q-PCR and Western immunoblot. Lysate exposure reduced PAO1 growth (∼5-fold) versus trypticase soy broth (TSB), but also resulted in appearance of a protein in culture supernatants, but not bacterial cell pellets, which reacted with antibody raised against ExoS. T3SS-inducing media (TSBi) caused the expression and secretion of ExoS and ExoT. Heat-treated lysates induced the protein; 1:3 diluted lysates did not. The protein that bound anti-ExoS antibody was found in supernatants of lysate-exposed exoT mutants, but not exoS or pscC mutants, suggesting a secreted form of ExoS, albeit slightly larger than that induced by TSBi. Lysate-exposed strain PAK expressed the same protein. Lysates caused PAO1 exoS and exoT gene expression, but only ∼20% and ∼6% of TSBi, respectively. T3SS induction by epithelial cell lysates could help explain T3SS expression by internalized P. aeruginosa . Abstract : Lysed epithelial cells induce expression of the Pseudomonas aeruginosa type three secretion system.